Squatting to end domicide? Resisting bulldozer urbanism in contemporary Shanghai - Zhang, Yunpeng (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
For millions of Shanghainese on the lower rung of society, the history of the great urban transformation in the city since the 1990s is written with their tears for the loss of their homes, communities and livelihood. In this paper, I argue for squatting as a straightforward, effective and potentially radical strategy to redress the displacees’ suffering, to take a more active and progressive control of the violent accumulation process and to challenge the hegemonic discourse of private homeownership that underpins the rapid transformation of Shanghai’s urban landscape. The argument is built upon an in-depth study of a family evicted by the World Expo 2010 and squatted in a resettlement apartment. Their framing of justice and entitlement, embedded in local cultural and moral universes, not only lends legitimacy to their squatting but also mobilises popular sympathy, both of which are conducive to effective resistance.